Brain injury, behaviour support, and family involvement: putting the pieces together and looking forward. Issue 9 (23rd April 2020) - Fisher, Alinka; Bellon, Michelle; Lawn, Sharon; Lennon, Sheila
Abstract: Purpose: (1) to provide insight into the family's experience and support needs following acquired brain injury (ABI) specific to behavioural changes; (2) to provide an overview of empirically-based behaviour support approaches for individuals with ABI; and (3), to examine family involvement in implementing behavioural interventions. Methods: Review of the literature. Results: Family members experience significant distress resulting from neurobehavioural changes in relatives with ABI, and report unmet informational and practical support needs regarding this issue. The importance of utilising family expertise within the rehabilitation process is widely acknowledged, with the increasing involvement of family members being promoted. There is growing evidence supporting the use of positive behaviour support approaches for individuals with ABI in community settings, and evidence supporting the involvement of family within behavioural interventions. Conclusions: This review suggests the need to develop alternative support models that shift the focus towards building competence in everyday support people rather than dependency on the service system. A bottom-up approach is recommended, with the aim of addressing unmet support needs and increasing the competence of family members in supporting behaviour change in individuals with ABI. Recommendations are provided in informing an optimal community-based neurobehavioural support model. Implications for Rehabilitation: Positive behaviour support is recommended in supporting behavioural changes following brain injury, with family expertise utilised in this process. Evidence suggests that family members can be effectively trained in developing and implementing behaviour support strategies. Family involvement in behavioural interventions may address unmet support needs and increasing the competence of family members in supporting behavioural changes following brain injury.